Pemaknaan ritual adat pujan kapitu oleh masyarakat Desa Ngadisari Kabupaten Probolinggo - anny mudahyana; nur hadi; deny wahyu apriadi (Departemen Pendidikan Sosiologi FISHIPOL UNY, 2024)
Indonesian communities continue to preserve various traditional rituals as part of their social and spiritual lives. One such community that has maintained this tradition to this day is the Tengger people through their traditional Pujan Kapitu ritual. This ritual is performed at the beginning of the seventh month of the Tengger calendar and holds great significance for the residents of Ngadisari Village. This study aims to understand the process of performing the Pujan Kapitu ritual and the symbolic meanings it embodies. The study employed a descriptive qualitative method, with data collected through observation and interviews. Research informants were selected using purposive sampling. The analysis was grounded in Herbert Blumer’s theory of symbolic interaction. The results show that the Pujan Kapitu procession is opened by a traditional shaman with a prayer and the offering of ritual gifts, followed by megeng or a strict vegetarian fast throughout the seventh month, and concluded with a prayer and ritual offerings at the village head’s house. The ritual’s significance includes enhancing spirituality, honoring ancestors, and maintaining harmony among all living beings and the environment.